Essential German grammar - Durrell, Martin; Kaiser, Claudia (Language specialist); Kohl, Katrin M (Katrin Maria) 1956-; Loftus, Gudrun (London New York Routledge, Taylor & Francis Group, 2015)
"This is a student-friendly grammar designed to give intermediate level-plus learners a firm foundation for developing their German language skills. Key features include: reference grammar section offering clear explanations, authentic texts from a range of media, helpful examples and tables; exercise section for practice; glossary of key grammatical terms. This new edition offers: grammatical explanations and passages revised in line with teaching practice, with some brand-new texts; an improved and accessible layout design; companion website offering many resources including interactive exercises and instructor materials. It is suitable for both classroom use and self-study"--
Includes index
1
Keywords: German language -- Grammar; German language -- Usage; LANGUAGE ARTS & DISCIPLINES / General